Variation in the Perceived Motor Self-Efficacy of Spanish Students throughout the Different Educational Stages - Carmen Galán-Arroyo; Irene Polo-Campos; Santiago Gómez-Paniagua; Jorge Rojo-Ramos (e-Motion: Revista de Educación, Motricidad e Investigación, 2023)
Motor self-efficacy is the ability to cope with obstacles, to control them and to solve them in the best possible way. It is closely related to performance in physical education and student health.  The aim of this study is to measure the performance of motor self-efficacy in Physical Education in students aged 10 to 18 years, analyzing the differences between students according to their educational level and age. A total of 946 students responded to five socio-demographic questions, in addition to the Motor Self-Efficacy Scale validated in Spanish. The Kolmogorov-Smirnov test was used to determine the assumption of normality, but since this assumption was not met, non-parametric tests were used. In this sense, the Motor Self-Efficacy Scale score and the differences between the different instructional cycles were analyzed using the Kruskal-Wallis test. In addition, a pairwise comparison was performed as part of a post hoc study to examine the differences between the different groups. The relationship between the mean scale score and the variable age was investigated using Spearman's Rho test. Subsequently, the relationship between motor self-efficacy and participants' height, weight and BMI was examined using the direct stepwise regression test. Finally, Cronbach's alpha was used to assess the reliability of the instrument. Significant statistical differences were observed between educational levels and their relationship with BMI, height and weight, highlighting the importance of motor self-efficacy at different stages. Therefore, it would be interesting to introduce educational methodologies that promote active models and improve students' motor self-efficacy.